Perancangan Sistem Monitoring dan Kontrol Otomatis Greenhouse Hidroponik Berbasis IoT - Aqhilah Astri; Gladys Maria; Muhammad Junaidi; Aqillah Meilika Putri; Verdi Riskiandi; Jihan Shona Zehran (Riau Jurnal Teknik Informatika, 2026)
The development of the Internet of Things (IoT) has encouraged the adoption of technology in the agricultural sector, particularly in hydroponic greenhouse systems. Manual control of temperature, humidity, light intensity, and other environmental conditions often reduces the effectiveness of crop cultivation. This study presents the design of an IoT-based hydroponic greenhouse monitoring and automatic control system. The research method consisted of a literature review, system requirements analysis, and the design of both hardware and software components. The proposed system employs an Arduino Uno as the main microcontroller, environmental sensors to monitor greenhouse conditions, and an ESP8266 module for data communication via the Internet. The design results include the hardware architecture, software workflow, and an automatic monitoring and control mechanism that enables real-time environmental data to be displayed through an Android application. The proposed system design is expected to serve as a reference for the future development and implementation of IoT-based smart hydroponic greenhouse systems.